Impact of Provocation Doctrine in the Crimes of Honor between Retention and Annulment: A Comparative Study of Arab Criminal Legislation - Al-Hassan, Abdul-Aziz (Women & criminal justice, 2023)
In this research, as a comparative study, we dealt with the excuse of provocation related to the issue of femicide against the background of so-called honor crimes, and the extent to which the perpetrator benefited from the valid or mitigating excuse. After identifying the meaning of “honor crimes,” we monitored the conditions for applying this excuse, the scope of its personal and objective application, and the punishment in Arab positive laws. We have also treated the recent legislative trends represented in the abolition of this excuse in some Arab laws and stated that it is an important step toward fairness for women, but it is not sufficient and requires other steps, so there is no limit to the adoption of a clear legislative plan with goals aimed at reaching radical remedies and decisive solutions that do not accept cutting or acting with ill-considered reactions, and in line with the provisions of Islamic law and relevant international agreements.